Co-Designing Immersive Experiences for Cultural Heritage: A User-Centric VR Approach for Intelligent Cultural Tourism (Architecture Image Studies, 2025)
This project introduces a computational, user-centered co-design methodology for creating immersive Virtual Reality (VR) media aimed at augmenting cultural tourism and education at a Khmer heritage site in Surin, Thailand. The study specifically focused on two objectives: (1) to connect digital media with authentic cultural interpretation by incorporating local requirements, and (2) to provide an accessible VR intelligent platform for community empowerment and cultural dissemination. The design thinking paradigm highlighted stakeholder preferences for mobile accessibility, modern aesthetics, and culturally concise narratives in development. The VR prototype for the Si Khor Phum Temple includes 360° tours and interactive 3D models, affirming its function as an accessible Human-Computer Interaction (HCI) instrument. Validation affirmed the system's quality and effectiveness. Expert assessments resulted in an exceptional overall quality rating, achieving flawless marks in linguistic clarity and system reliability. User testing validated elevated satisfaction levels, particularly with engagement. The research presents a proven participatory system design model that illustrates VR's potential as an adaptive tool for immersive education, historical preservation, and a significant driver of community empowerment via locally grounded digital innovation.